2022
DOI: 10.3389/fneur.2022.917845
|View full text |Cite
|
Sign up to set email alerts
|

Acute Unilateral Peripheral Vestibulopathy After COVID-19 Vaccination: Initial Experience in a Tertiary Neurotology Center

Abstract: ObjectiveThe aim of the present study was to identify patients who developed acute unilateral peripheral vestibulopathy (AUPVP) after COVID-19 vaccination.MethodsFor this single-center, retrospective study, we screened the medical records of our tertiary interdisciplinary neurotology center for patients who had presented with AUPVP within 30 days after COVID-19 vaccination (study period: 1 June−31 December 2021). The initial diagnosis of AUPVP was based on a comprehensive bedside neurotological examination. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 70 publications
(103 reference statements)
0
8
1
Order By: Relevance
“…Due to the suspected immunological cause, with reactivation of herpes simplex virus (HSV) type II from the vestibular ganglion [ 28 ], acute UVP following vaccination appears to be an interesting subgroup. A recent study by Schmid et al found eight patients in a 6‐month period who had developed a UVP in timely conjunction with COVID‐19 vaccination [ 14 ]; in our patient subcohort, only three patients suffered from a UVP after their vaccination (within a 4‐week interval), which was less frequent than in the prepandemic control cohort. Although we cannot exclude that the inflammatory response to COVID‐19 vaccination may contribute to the evolution of a vestibular neuritis by reactivation of HSV II in single cases, a specific clustering above likelihood of spontaneous incidence was not observed.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Due to the suspected immunological cause, with reactivation of herpes simplex virus (HSV) type II from the vestibular ganglion [ 28 ], acute UVP following vaccination appears to be an interesting subgroup. A recent study by Schmid et al found eight patients in a 6‐month period who had developed a UVP in timely conjunction with COVID‐19 vaccination [ 14 ]; in our patient subcohort, only three patients suffered from a UVP after their vaccination (within a 4‐week interval), which was less frequent than in the prepandemic control cohort. Although we cannot exclude that the inflammatory response to COVID‐19 vaccination may contribute to the evolution of a vestibular neuritis by reactivation of HSV II in single cases, a specific clustering above likelihood of spontaneous incidence was not observed.…”
Section: Discussioncontrasting
confidence: 45%
“…However, its proportion corresponds to the usual frequency at our [14]; in our patient subcohort, only three patients suffered from a UVP after their vaccination (within a 4-week interval), which was less frequent than in the prepandemic control cohort. Although we cannot exclude that the inflammatory response to COVID-19 vaccination may contribute to the evolution of a vestibular neuritis by reactivation of HSV II in single cases, a specific clustering above likelihood of spontaneous incidence was not observed.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Olfactory dysfunction 15 (30) Gustatory dysfunction 21 ( considered their infection as "mild", and 36 patients (72%) reported olfactory and gustatory symptoms. The other patient who received inpatient or ICU treatment described their infection as "severe".…”
Section: Symptoms Covid-19mentioning
confidence: 99%
“…Further research is needed to clarify if LD and other neurotropic infections are one of the causes of VN. Since the COVID-19 pandemic, there are also reports about VN after COVID-19 infection and after vaccination [28] and the reports about its neurotropic potential accumulate. Therefore it is essential to test patients with acute onset of peripheral vestibular neuropathy also for COVID-19.…”
Section: Laboratory Findingsmentioning
confidence: 99%